Utilization of Probiotic and Organic-Cn on Ruminal Ecosystem In Vitro - Wulansih Dwi Astuti; Roni Ridwan; Baharuddin Tappa (Jurnal Ilmu Ternak dan Veteriner, 2007)
Improvement of nutrient intake was needed to increase cattle productivity. Probiotics and organic Cr, as feed additives, might have beneficially improve ruminant microbial ecosystem, and optimize digestion process by rumen microbes. The objective of this study was to examine the effects of combination between probiotic or mixed probiotcs and organic Cr on rumen fermentation activity. An in vitro study was held based on randomized block design with 5 treatments and 3 replications. The treatments were (A) Control ration, (B) Control ration + probiotic TSD 10, (C) Control ration + probiotic TSD 10 + organic Cr, (D) Control ration + mixed probiotics, and (E) Control ration + mixed probiotics + organic Cr. Organic Cr concentration was supplemented 2 ppm, whereas probiotics supplement contained 109 cfu/g. Supplementation of probiotic and organic Cr increased dry matter and organic matter digestibility but decreased total VFA and NH3 concentration. Treatment E (combination between mixed probiotics and organic Cr) gave the highest dry matter (52.45 %) and organic matter (51.96 %) digestibilities. It also tended to increase NH3 and total VFA production. Supplementation of single or mixed probiotics showed no difference for dry matter and organic matter digestibilities, and proportion of individual VFA. Mixed probiotics gave higher VFA and NH3 concentration compared to single probiotic. Probiotics supplementation resulted in a tendency for higher acetate proportion, while organic Cr supplementation resulted in a tendency of higher propionate proportion. Key Words: Probiotic, Organic Cr, Ruminal Microbes, VFA